MFRP variations cause nanophthalmos in five Chinese families with distinct phenotypic diversity - Li, Zhen; Ma, Runqing; Ma, Meijiao; Xiao, Xue; Qi, Xiaolong; Ma, Hongjuan; Sheng, Xunlun; Rong, Weining (Frontiers in Genetics, 2024)
Purpose Nanophthalmos is a congenital ocular structural anomaly that can cause significant visual loss in children. The early diagnosis and then taking appropriate clinical and surgical treatment remains a challenge for many ophthalmologists because of genetic and phenotypic heterogeneity. The objective of this study is to identify the genetic cause of nanophthalmos in the affected families and analyze the clinical phenotype of nanophthalmos with MFRP gene variation (Microphthalmia, isolated; OMIM#611040 and Nanophthalmos 2; OMIM#609549, respectively). Methods Comprehensive ophthalmic examinations were performed on participants to confirm the phenotype. The genotype was identified using whole exome sequencing, and further verified the results among other family members by Sanger sequencing. The normal protein structure was constructed using Alphafold. Mutant proteins were visualized using pymol software. Pathogenicity of identified variant was determined by in silico analysis and the guidelines of American College of Medical Genetics and Genomics (ACMG). The relationship between genetic variants and clinical features was analyzed. Results Five nanophthalmos families were autosomal recessive, of which four families carried homozygous variants and one family had compound heterozygous variants in the MFRP gene. Both family one and family three carried the homozygous missense variant c.1486G>A (p.Glu496Lys) in the MFRP gene (Clinvar:SCV005060845), which is a novel variant and evaluated as likely pathogenic according to the ACMG guidelines and in silico analysis. The proband of family one presented papilloedema in both eyes, irregular borders, thickened retinas at the posterior pole, tortuous and dilated retinal vessels, and indistinguishable arteries and veins, while the proband of family three presented uveal effusion syndrome-like changes in the right eye. In families one and 3, despite carrying the same gene variant, the probands had completely different clinical phenotypes. The homozygous nonsense variant c.271C>T (p.Gln91Ter) (Clinvar:SCV005060846) of the MFRP gene was detected in family 2, presenting shallow anterior chamber in both eyes, pigmentation of peripheral retina 360° from the equator to the serrated rim showing a clear demarcation from the normal retina in the form of strips. Family four proband carried the homozygous missense variant c.1411G>A (p.Val471Met) in the MFRP gene (Clinvar:SCV005060847), family five proband carried compound heterozygous missense variants c.1486G>A (p.Glu496Lys) and c.602G>T (p.Arg201Leu) in the MFRP gene (Clinvar:SCV005060848), which is a novel variant and evaluated as likely pathogenic according to the ACMG guidelines and in silico analysis, and they all presented clinically with binocular angle-closure glaucoma, family four also had retinal vein occlusion in the right eye during the follow-up. Conclusion In this study, pathogenic variants of the MFRP gene were detected in five nanophthalmos families, including two novel variants. It also revealed a distinct phenotypic diversity among five probands harboring variants in the MFRP gene. Our findings extend the phenotype associated with MFRP variants and is helpful for ophthalmologists in early diagnosis and making effective treatment and rehabilitation strategies.